A Comparison of CT-Scan Output Doses and Doses Given to Kidney Stone Patients - Ronel Arida Missinychrista; Kadek Subagiada; Erlinda Ratnasari Putri (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Kidney stones are a disease which occurs in the urinary tract and are hard accumulations like stones that form along the urinary tract and can cause pain, bleeding, obstruction to the flow of urine or infection. Generally, the method of diagnosis given by doctors to patients with kidney stones is through a CT scan. However, so far it is not known how much radiation the patient receives during the CT scan procedure. Therefore, in this study an analysis was carried out regarding the comparison of the dose issued by the CT-Scan with the dose received by the patient on the CT-Abdomen examination, an analysis of the patient dose based on the SSDE value on the CT-Abdomen examination, and an analysis of the total dose received by the patient on CT-Abdomen examination. The data used in this study is data downloaded from the official website page of the "Data Science Institute American College of Radiology" at https://www.acr.org/. Based on the results of existing research, the researchers drew the conclusion that the doses released by the device tend to be lower than the doses received by patients, the maximum SSDE value is 28.7550 mGy and the minimum SSDE value is 6.7978 mGy, the maximum DLP value is of 657.1314 mGy.cm and the minimum DLP value is 62.5992 mGy.cm. This should be a concern for radiation workers to pay attention to the dose received by the patient during the examination.